Analisis Kualitas Website MyHerbalife Menggunakan Metode Webqual 4.0 - Nyimas Sopiah; Fakhri Khoirullah Ardhana (Jurnal Ilmiah Matrik, 2025)
Entering the digital business especially in the marketing field caused by technological developments. One of the technologies that can help businesses in the marketing field is the website. The formulation of the problem in this study which focuses on the MyHerbalife website is that the researcher will also analyze the quality of the MyHerbalife website whether it makes it easy for customers to purchase products through the website and whether MyHerbalife has a decent website. The purpose of this study is to analyze the quality of the feasibility of using the MyHerbalife website by applying the WebQual method. The method used in this study is Webqual which includes Usability, Information Quality, Service Interaction. The results obtained from this study are that the Usability variable of usability quality has a large impact on the Overall Impression variable of user satisfaction, from the Information Quality side indicates that the information variable has a large impact on the Overall Impression variable of user satisfaction, and from the Service Interaction Quality side indicates that the Service Interaction Quality variable of service quality has a large impact on the Overall Impression variable of user satisfaction.